Hybrid modeling and control of three-level NPC rectifiers. (January 2023) - Montero-Robina, Pablo; Albea, Carolina; Gómez-Estern, Fabio; Gordillo, Francisco
Abstract: This article revisits the modeling of the grid-connected neutral point-clamped converter as a time-varying nonlinear hybrid dynamical system. As a result, an embedded control law that guarantees stability and fulfills the control objectives, namely dc-link voltage regulation, power-to-grid energy exchange and capacitor voltage balancing, is proposed. In addition, a rigorous study of stability is carried out without depending on an averaged model and considering the hybrid dynamical character of the system. Moreover, the hybrid control guarantees a minimum dwell time. This approach could be extended to other topologies or control laws in the search for rigorous stability guarantee The algorithm is evaluated and tested experimentally, verifying the feasibility of the approach. This process involves adapting the algorithm to be programmed in a FPGA as well as some further modifications to improve the steady-state performance. The experimental results are performed under several reference changes and perturbations to prove the feasibility of the proposed approach.